Investigating the Efficacy of Information System Integration for Electronic Medical Records in Enhancing Healthcare Quality - Tania Ratisari (Green Health International Journal of Health Sciences Nursing and Nutrition, 2024)
This study delves into the intricacies of implementing information systems for electronic medical records (EMR) at Hospital Palangka Raya, emphasizing the importance of healthcare service quality. Using a descriptive research approach, the study gathered data from 60 questionnaires through simple random sampling from January 5 to January 25, 2023. The research instrument employed was a questionnaire, yielding insightful results on the agreement levels between reality and expectations across key variables like Man (90.12%), Machine (85.75%), Method (90.06%), Material (90.18%), and Environment (90.94%). Based on these findings, the study recommends regular evaluations every six months, coupled with training and collaboration initiatives, to enhance EMR implementation and improve Electronic Medical Records' quality